Amino acid modified OCMC-g-Suc-β-CD nanohydrogels carrying lapatinib and ginsenoside Rg1 exhibit high anticancer activity in a zebrafish model - Li Cui; Li Cui; Xiaolan Liu; Rongjun Yan; Qixu Chen; Lizhen Wang; Shah Nawaz; Dawei Qin; Daijie Wang; Daijie Wang (Frontiers in Pharmacology, 2023)
Nanohydrogels show great potential as efficient drug carriers due to their biocompatibility, low toxicity, and high water absorbability. In this paper, we prepared two O-carboxymethylated chitosan (OCMC)-based polymers functionalized with β-cyclodextrin (β-CD) and amino acid. The structures of the polymers were characterized by Fourier Transform Infrared (FTIR) Spectroscopy. Morphological study was carried out on a Transmission Electron Microscope (TEM), and the results indicated that the two polymers had irregular spheroidal structure with some pores distributed on their surface. The average particle diameter was below 500 nm, and the zeta potential was above +30 mV. The two polymers were further used for preparing nanohydrogels loaded with anticancer drugs lapatinib and ginsenoside Rg1, and the resulting nanohydrogels showed high drug loading efficiency and pH-sensitive (pH = 4.5) drug release behavior. In vitro cytotoxicity investigation revealed that the nanohydrogels exhibited high cytotoxicity against lung cancer (A549) cells. In vivo anticancer investigation was performed in a transgenic Tg(fabp10:rtTA2s-M2; TRE2:EGFP-krasV12) zebrafish model. The results showed that the synthesized nanohydrogels significantly inhibited the expression of EGFP-krasv12 oncogene in zebrafish liver, and the L-arginine modified OCMC-g-Suc-β-CD nanohydrogels loading lapatinib and ginsenoside Rg1 showed the best results.